Downregulated MicroRNA-327 Attenuates Oxidative Stress-Mediated Myocardial Ischemia Reperfusion Injury Through Regulating the FGF10/Akt/Nrf2 Signaling Pathway - Tao Zheng; Jun Yang; Jun Yang; Jing Zhang; Chaojun Yang; Zhixing Fan; Qi Li; Yuhong Zhai; Haiyin Liu; Jian Yang (Frontiers Media S.A., 2021)
Although miR-327 had a protective effect on cardiomyocytes as described previously, the potential mechanism still needs further exploration. The aim of this study was to investigate the role and mechanism of miR-327 on oxidative stress in myocardial ischemia/reperfusion injury (MI/RI) process. Oxidative stress and cardiomyocytes injury were detected in rat model of MI/RI, hypoxia/reoxygenation (H/R), and tert-butyl hydroperoxide (TBHP) model of H9c2 cells. In vitro, downregulation of miR-327 inhibited both H/R- and TBHP-induced oxidative stress, and suppressed apoptosis. Meanwhile, fibroblast growth factor 10(FGF10) was enhanced by miR-327 knocked down, followed by the activation of p-PI3K and p-Akt, and the translocation of Nrf2. However, miR-327 overexpression performed with opposite effects. Consistent with the results in vitro, downregulation of miR-327 attenuated reactive oxygen species (ROS) generation as well as intrinsic apoptosis, and alleviated I/R injury. In conclusion, inhibition of miR-327 improved antioxidative ability and myocardial cell survival via regulating the FGF10/Akt/Nrf2 pathway.